PREPARATION AND EVALUATION OF IRBESARTAN-CYCLODEXTRIN INCLUSION COMPLEXES - Hirlekar, Rajashree; Kadam, V J (Journal of Drug Delivery and Therapeutics, 2017)
In the present work effect of methyl-Î²-cyclodextrin (MÎ²CD) on physical properties and dissolution rate of Irbesartan (IRB) was studied.Based on AL-type ofphase solubility diagram obtained, solid binary systems of the drug with MÎ²CD were prepared in 1:1 molar ratio by various methods. Complexes were characterized using Differential Scanning Calorimetry and powder X-Ray Diffractometry. It could be concluded that IRB can form inclusion complex with MÎ²CD. The dissolution profiles of inclusion complexes were compared with those of IRB alone and the physical mixture. The dissolution rate of IRB was increased remarkably by MÎ²CD inclusion complexation.